Penerapan Konsep Wu Xing Dalam Perancangan Interior Oriental Wedding Center di Surabaya - Batari, Indri (Intra, 2015)
The economy and infrastructure development in Surabaya have resulted the high activity and mobility of people. Everything is demanded to be fast, flexible, efficient, and productive. Various needs of people arouses between the activities, including the need of wedding preparation. By prioritizing the fulfillment of function in an oriental concept wedding, remembering the low availability of wedding facility with the oriental atmosphere. This place have a lot of facilities such as lobby, consultation room, gallery, and Meeting area. The concept of Wedding center is Wu Xing.There are five elements inside Wu Xing, wood, fire, land, steel, and water. If all element become one and achieved the balance, the outcome will be a good energy. This Wedding center can be alternate place for couple to prepare their wedding in oriental style.